Precedentes judiciais na justiça do trabalho: uma análise da sua formação a partir das formas de participações democráticas - Souza, Luiza Baleeiro Coelho (2020)
To achieve greater legal certainty and resolve practical problems related to the increasing judicialization, the Brazilian procedural legal system underwent several changes, culminating, the greatest of them, in the edition of CPC/2015, which brought with it a system of binding precedents. Contemporary to the new code, the CLT was amended by Law nº 13.015/14, responsible for incorporating this new system into the labor procedural law. Although making binding decisions was not entirely new, there was clearly an increase in the list of possibilities in which these decisions could be formed. This situation should be viewed cautiously from a democratic perspective, especially in a context of prominence of the Judiciary to the detriment of a decrease in popular participation in the legislative process. In this scenario, the present research aims to verify if the precedents that are being built before the Tribunal Superior do Trabalho can be considered democratic based on the theory of democracy by Jürgen Habermas, the author chosen as a theoretical framework. Therefore, the work was developed from the use of qualitative methodology through the use of bibliographic technique and case study, seeking a theoretical and practical integration on the proposed theme.